OPTIMASI BIAYA & WAKTU PADA PENJADWALAN PROYEK PERUMAHAN DENGANMICROSOFT PROJECT (Studi kasus : Perumahan Cluster Pamulang) - Muhammad Banu Resta (CV. ADIBA AISHA AMIRA, 2023)
Cost and time are benchmarks for project success and failure. This is evidenced by the fact that the quality of the work is not compromised, and is completed in a short time at minimal cost. Therefore, time and cost optimization efforts are very important when planning a project. One way to optimize time and costs is the crash method. Crashing is a deliberate, systematic, and analytical process through which testing accelerates all activities in a project focusing on activities that are on the critical path. In this study, we used the Microsoft Project 2021 program to optimize time and costs. By entering survey data into the program, this Microsoft Project will automatically perform calculations, resulting in more accurate calculations., Faster and More Accurate Findings from the Pamrang Cluster Housing Project show that the accelerated implementation has resulted in a reduction in indirect and overall project costs. From the calculation results, the optimal project completion time is 115.96 working days (144 calendar days) and the total project cost is IDR 361,005,732.00. While the normal completion time is 136.08 working days (68 calendar days) and the total project cost is IDR 364,091,924.-. This will reduce runtime for 24 days and reduce costs by IDR 3,086,192.00.